2002
DOI: 10.1097/00002093-200210000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Relative Frequencies of Alzheimer Disease, Lewy Body, Vascular and Frontotemporal Dementia, and Hippocampal Sclerosis in the State of Florida Brain Bank

Abstract: Alzheimer disease (AD) is the most common dementing illness in the elderly, but there is equivocal evidence regarding the frequency of other disorders such as Lewy body disease (LBD), vascular dementia (VaD), frontotemporal dementia (FTD), and hippocampal sclerosis (HS). This ambiguity may be related to factors such as the age and gender of subjects with dementia. Therefore, the objective of this study was to calculate the relative frequencies of AD, LBD, VaD, FTD, and HS among 382 subjects with dementia from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
388
3
23

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(433 citation statements)
references
References 59 publications
12
388
3
23
Order By: Relevance
“…How well our results may generalize to the aged population at large is unknown, but in this context the heterogeneity of this sample is strength. Community-based studies using autopsy confirmation of diagnosis have generally shown a substantial frequency of cases with "mixed dementia," with reported rates ranging from 40% to 77% (Barker et al, 2002;White et al, 2005). Some degree of caution about the generalizability of the results does seem warranted given differences between the study and parent samples.…”
Section: Discussionmentioning
confidence: 95%
“…How well our results may generalize to the aged population at large is unknown, but in this context the heterogeneity of this sample is strength. Community-based studies using autopsy confirmation of diagnosis have generally shown a substantial frequency of cases with "mixed dementia," with reported rates ranging from 40% to 77% (Barker et al, 2002;White et al, 2005). Some degree of caution about the generalizability of the results does seem warranted given differences between the study and parent samples.…”
Section: Discussionmentioning
confidence: 95%
“…In a pathological study of 382 brains of individuals with dementia who were referred to the State of Florida Brain Bank, the vast majority (77%) had a pathological diagnosis of AD (Barker et al 2002). Of these, 54% had "pure" AD pathology, whereas concomitant pathologies (e.g., Lewy body or vascular disease) were detected in the remainder.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Of these, 54% had "pure" AD pathology, whereas concomitant pathologies (e.g., Lewy body or vascular disease) were detected in the remainder. Additionally, AD pathology was present in most cases of dementia with Lewy bodies (DLB) (66%) and vascular dementia (77%) (Barker et al 2002).…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Many diseases can cause dementia, but Alzheimer's disease (AD) is the most common [2,3]. Vascular dementia and dementia with Lewy bodies (DLB) are the next most common [2,3] whilst frontotemporal lobar degeneration (FTLD) is the third most common dementing disease under 65 years [4].…”
Section: Introductionmentioning
confidence: 99%